Brief Report: The Role of Rare Protein‐Coding Variants in Anti–Tumor Necrosis Factor Treatment Response in Rheumatoid Arthritis. Issue 4 (29th March 2017) - Cui, Jing; Diogo, Dorothee; Stahl, Eli A.; Canhao, Helena; Mariette, Xavier; Greenberg, Jeffrey D.; Okada, Yukinori; Pappas, Dimitrios A.; Fulton, Robert S.; Tak, Paul P.; Nurmohamed, Michael T.; Lee, Annette; et al.
Abstract : Objective: In many rheumatoid arthritis (RA) patients, disease is controlled with anti–tumor necrosis factor (anti‐TNF) biologic therapies. However, in a significant number of patients, the disease fails to respond to anti‐TNF therapy. We undertook the present study to examine the hypothesis that rare and low‐frequency genetic variants might influence response to anti‐TNF treatment. Methods: We sequenced the coding region of 750 genes in 1, 094 RA patients of European ancestry who were treated with anti‐TNF. After quality control, 690 genes were included in the analysis. We applied single‐variant association and gene‐based association tests to identify variants associated with anti‐TNF treatment response. In addition, given the key mechanistic role of TNF, we performed gene set analyses of 27 TNF pathway genes. Results: We identified 14, 420 functional variants, of which 6, 934 were predicted as nonsynonymous 2, 136 of which were further predicted to be "damaging." Despite the fact that the study was well powered, no single variant or gene showed study‐wide significant association with change in the outcome measures disease activity or European League Against Rheumatism response. Intriguingly, we observed 3 genes, of 27 with nominal signals of association ( P < 0.05), that were involved in the TNF signaling pathway. However, when we performed a rigorous gene set enrichment analysis based on association P value ranking, we observed no evidence of enrichment of association at genes involved in the TNF pathway ( P enrichment = 0.15, based on phenotype permutations). Conclusion: Our findings suggest that rare and low‐frequency protein‐coding variants in TNF signaling pathway genes or other genes do not contribute substantially to anti‐TNF treatment response in patients with RA.